2016
DOI: 10.1007/s12551-015-0188-0
|View full text |Cite
|
Sign up to set email alerts
|

The structural stability and catalytic activity of DNA and RNA oligonucleotides in the presence of organic solvents

Abstract: Organic solvents and apolar media are used in the studies of nucleic acids to modify the conformation and function of nucleic acids, to improve solubility of hydrophobic ligands, to construct molecular scaffolds for organic synthesis, and to study molecular crowding effects. Understanding how organic solvents affect nucleic acid interactions and identifying the factors that dominate solvent effects are important for the creation of oligonucleotide-based technologies. This review describes the structural and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 125 publications
4
76
0
Order By: Relevance
“…According to the literature, PEG2000 and similar molecules do not produce significant excluded volume effects, but they do show different degrees of hydrogen bonding, polarity, and hydrophobicity. Therefore, the addition of PEG2000 to water could create co‐solvent–co‐solvent and water–co‐solvent interactions and interrupt water–water interactions that stabilise nucleic acid complexes . However, upon comparing the ON5+ON6 and ON7+ON8 systems, it was found that the system with the Cy3/Cy5 pair was more stable upon adding polylysine and PEG.…”
Section: Resultssupporting
confidence: 89%
“…According to the literature, PEG2000 and similar molecules do not produce significant excluded volume effects, but they do show different degrees of hydrogen bonding, polarity, and hydrophobicity. Therefore, the addition of PEG2000 to water could create co‐solvent–co‐solvent and water–co‐solvent interactions and interrupt water–water interactions that stabilise nucleic acid complexes . However, upon comparing the ON5+ON6 and ON7+ON8 systems, it was found that the system with the Cy3/Cy5 pair was more stable upon adding polylysine and PEG.…”
Section: Resultssupporting
confidence: 89%
“…This result indicates that many kinds of organic additives are useful for enhancing the turnover activity of the hammerhead ribozyme. It has been reported that the stability of base pairing and tertiary folding is reduced in the presence of organic solvents, particularly amide compounds that are known to substantially destabilize nucleic acid structures [31,44]. However, this destabilization effect seemed not to cause a disruption of interactions necessary for the formation of the active conformation, such as a network of hydrogen bonds [48], in the presence of 10 mM MgCl 2 .…”
Section: Effects On the Hammerhead Ribozymementioning
confidence: 99%
“…These organic additives may alter the physical properties of solution, interact with nucleic acids, and introduce areas of excluded volume [20,31]. Most mixed solutions have lower dielectric constant values than pure water, and the additives, such as large PEGs, MME, DME, EtOH PrOH, and DOX, significantly lowers the dielectric constant of solution.…”
Section: Classification Of the Mixed Solutions Based On The Effects Omentioning
confidence: 99%
“…With the use of crowder molecules such as poly(ethylene glycol)s (PEGs) to mimic intracellular crowding conditions, it has been clarified that DNA duplex thermal stabilities decrease due to a decrease in the water activity [ 15 , 16 , 17 ]. Molecular crowding also decreases the dielectric constant of the solution, which can increase the ribozyme activities [ 18 , 19 ]. In polymerase reactions, we found that the efficiency and preference of RNA primer extension along the RNA or DNA template by RNA polymerases were drastically affected by molecular crowding [ 20 ]: T7 RNA polymerase preferentially incorporated dNTPs over NTPs along the RNA template under specific crowding conditions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%